(untitled) (Journal of Organizational Psychology, 2020)
This comparative study of NPOs in the U. S. and South Korea uses social exchange and labor donation theories along with Hofstede’s cultural values to identify differences in preferences for human resource practices in these two countries. Results indicate that South Korean nonprofit employees showed greater preference for HR practices related to work design than U.S. nonprofit employees, while U.S. nonprofit employees showed greater preferences for HR practices designed to manage employee attitudes and behaviors. The findings of this study provide important information for the design of HR practices in nonprofits involved in global expansion and/or operations in multinational settings.